Graphene Quantum Dots (GQDs) for Bioimaging and Drug Delivery Applications: A Review - Biswas, Manik Chandra; Islam, Md Tariqul; Nandy, Pranab Kumar; Hossain, Md Milon (ACS materials letters, 2021)
Quantum dots (QDs) exhibit unique physicochemical and optical properties that are suitable for photovoltaic cells, light-emitting diodes, and optoelectronic devices; however, unlike selenium and tellurium/metal-sulfide-based QDs, graphene quantum dots (GQDs) are comparatively less toxic and biocompatible, making them promising candidates for biological applications such as bioimaging, drug delivery agents, therapeutics, and theranostics. Various synthesis techniques such as top-down and bottom-up methods along with novel green synthesis methods for the preparation of pure and doped GQDs are thoroughly discussed in this study. Physicochemical, optical, and biological properties such as size- and chemical-composition-dependent fluorescence, therapeutics, disease diagnostics, biocompatibility, and cellular toxicity are extensively studied and summarized. Finally, the prospects and potential directions of GQDs in drug delivery and bioimaging systems are discussed in regards to challenges such as the synthesis, biocompatibility, and cellular toxicity.